2010
DOI: 10.1007/s10554-010-9729-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (≥2 years) follow-up optical coherence tomographic study after sirolimus- and paclitaxel-eluting stent implantation: comparison to 9-month follow-up results

Abstract: Many studies have demonstrated that late or very late thrombosis after drug-eluting stent (DES) implantation may be related with incomplete neointimal coverage. We investigated long-term (≥2 years) results of neointimal coverage following sirolimus-eluting stent (SES) and paclitaxel-eluting stent (PES) implantation using optical coherence tomography (OCT). A follow-up angiography with OCT examination was performed in 29 patients with 32 lesions for more than 2 years (group 1; 1,066 ± 381 days) and 101 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…One possible explanation for such late occurrence is incomplete neointimal coverage as a result of delayed arterial healing, ongoing vessel wall inflammation and late acquired stent malapposition [4650]. These phenomena have been observed in patients with DES by real-time imaging studies (angioscopy and optical coherence tomography (OCT)) [47, 4951] and also in some autopsy studies of stented segments in patients with very late ST [46]. Figure 2 demonstrates a definite ST in a patient 18 months following SES implantation and evidence of thrombus on malapposed struts.…”
Section: Predictors Of Stent Thrombosismentioning
confidence: 99%
“…One possible explanation for such late occurrence is incomplete neointimal coverage as a result of delayed arterial healing, ongoing vessel wall inflammation and late acquired stent malapposition [4650]. These phenomena have been observed in patients with DES by real-time imaging studies (angioscopy and optical coherence tomography (OCT)) [47, 4951] and also in some autopsy studies of stented segments in patients with very late ST [46]. Figure 2 demonstrates a definite ST in a patient 18 months following SES implantation and evidence of thrombus on malapposed struts.…”
Section: Predictors Of Stent Thrombosismentioning
confidence: 99%
“…Previous OCT studies reported that the percentage of uncovered struts was 15% at 3 months (19), 8.9% to 13.3% at 6 months (20 -22), and 12.2% at 9 to 12 months after SES implantation (23). In addition, until now, serial or long-term (Ն2 years) follow-up OCT studies after DES implantation were very rare and the number of study patients in those studies was smaller (16,25). As the time interval from stent implantation to follow-up OCT was longer, there was a trend toward decreased rate of uncovered struts in general.…”
Section: Figure 3 Serial Change Of Neointimal Tissue Patternmentioning
confidence: 99%
“…Recent studies show the lack of endothelial coverage of drug-eluting-stent even years after stent implantation. 2 It is believed that the persistently exposed stent struts may provide a nidus for infection during an episode of bacteremia. However, in this particular case, we postulate that previous stent fracture was a predisposing condition for the infection.…”
Section: Discussionmentioning
confidence: 99%